Microbial protein synthesis and nitrogen metabolism in cows bred on tropical pasture and fed on cassava root and corn - Silva, Ádler Carvalho da; Figueiredo, Mauro Pereira de; Bonomo, Paulo; Pereira, Mara Lúcia Albuquerque; Luz, Yann dos Santos; Santos, Edileusa de Jesus (Acta Scientiarum. Animal Sciences, 2014)
Current experiment evaluated the effect of replacement of full corn meal by dehydrated ground cassava roots at levels 0%, 25%, 50%, 75% and 100% in experimental supplements for lactating cows grazing on irrigated and fertilized tropical pastures. Ten Holstein cows were divided into two 5 x 5 Latin squares, with average initial 150 days of lactation, milk production 22±3.30 kg day-1 at the beginning of experiment and initial body weight of 603±65 kg. Cows were maintained on pasture consisting of elephant grass (Pennisetum purpureum, Schum) cultivar Pioneiro, intercropped with Tifton 85 (Cynodon nlemfuensis), fertilized with 600 kg nitrogen per hectare year-1. There was no significant difference (p > 0.05) between the substitution levels of corn meal by ground and dehydrated cassava root in the concentrate on the synthesis of microbial protein with an estimated average of 1,288.49 g day-1 and efficiency in the synthesis of microbial protein per kilogram of TDN with estimated average of 91.30 g kg-1 TDN. Nitrogen equilibrium showed an estimated average of 218.79 g day-1 of retained nitrogen. The microbial protein synthesis and nitrogen balance were not affected by treatments.